Restricted Coasean Bargaining - Ian A. MacKenzie; Markus Ohndorf (ETH Zurich, CER-ETH - Center of Economic Research, 2012)
We investigate the efficiency of Coasean bargaining when restrictions are placed on the set of feasible bargaining outcomes. When property rights are costly to (defend) appropriate, we find bargaining restrictions may be Pareto superior to unconstrained voluntary exchange. Under cost uncertainty over the externality, we show an efficient configuration of restrictions must balance the potential reduction in appropriation costs with the possibility of allocatively inefficient bargaining restrictions. For cases where the restrictions are contested, we show conditions for the continuing existence of welfare improvements.
Keywords: D62; D72; K1; 330; Coase theorem; bargaining restrictions; appropriation; Coase-Theorem; Pareto-Optimum; Externer Effekt; Verhandlungstheorie